Exploiting endogenous fibrocartilage stem cells to regenerate cartilage and repair joint injury - Mildred C. Embree (Nature Portfolio, 2016)
A potentially superior tissue regenerative strategy to stem cell transplantation is modulation of endogenous stem cells. Here the authors show fibrocartilage stem cells exist in the temporomandibular joint that contribute to cartilage regeneration and can be manipulated to enhance regeneration through canonical Wnt signalling.